The Hobbit, or, There and back again - Tolkien, J. R. R. (John Ronald Reuel), 1892-1973 (Ballantine Books, 1982)
The adventures of the well-to-do hobbit, Bilbo Baggins, who lived happily in his comfortable home until a wandering wizard granted his wish. Bilbo Baggins was a hobbit who wanted to be left alone in quiet comfort. But the wizard Gandalf came along with a band of homeless dwarves. Soon Bilbo was drawn into their quest, facing evil orcs, savage wolves, giant spiders, and worse unknown dangers. Finally, it was Bilbo -- alone and unaided -- who had to confront the great dragon Smaug, the terror of an entire countryside ...